A Daring Obedience: Ibn ʿArabī’s Futuwwa on the Right Side of the Law - Zargar, Cyrus Ali (Journal of Islamic ethics, 2020)
Abstract While Sufi writings have largely depicted futuwwa as the selfless virtue of upright young men, there has been, throughout Islam’s intellectual history, an underlying current characterised by brave rebelliousness, a current tied to the virtue’s complex relationship with urban fraternal societies. This paper investigates Muḥyī al-Dīn Ibn ʿArabī’s (d. 638/1240) deliberate response to futuwwa ’s implications of recalcitrance. Making a case for a law-abiding variety of the virtue, Ibn ʿArabī builds a theoretical frame in which this manly trait, one of consideration and altruism, mimics divine attributes, especially a divine calculating wisdom. In doing so, Ibn ʿArabī performs a role that Jeff Mitchell describes as the prerogative of noble elites, historically speaking, namely, the social construction of virtue. As is argued here, while Ibn ʿArabī makes a careful case for a law-abiding futuwwa , the lingering resonances of the virtue’s gangster associations indicate that social influence is, to a degree, reciprocal. That is, while Ibn ʿArabī’s framing of futuwwa makes a detailed and metaphysically-substantiated case for law-abidingness, his argument also suggests, however implicitly, that the virtue cannot completely escape its non-elite outlaw framework.